Meningkatkan Hasil Belajar Siswa Melalui Model Problem Based Learning Dalam Pembelajaran PAI Dan Budi Pekerti Kelas IV SD Negeri 11 Kampung Tujuh - Nedrawati, Nedrawati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) among fourth-grade students at SDN 11 Kampung Tujuh by implementing the Problem Based Learning (PBL) model. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. In the first cycle, the students' mastery level reached 50%, which increased to 70% in the second cycle. Although there was improvement, the results indicated that students' learning mastery had not yet achieved the predetermined success indicators. The main challenges were the lack of variety in learning media and the suboptimal delivery techniques. Reflections from both cycles demonstrated that the implementation of the PBL model effectively enhanced student engagement and critical thinking skills, yet further improvements are needed to meet the desired learning outcomes.